Mapping the invisible rape: Men and boys as victims of sexual violence in armed conflict - Garrido, R. (Nação e Defesa, 2021)
An armed conflict is always a scenario of extreme violence. From all forms of violence, the rape is one with tremendous power of destruction of the individual and collective, disaggregating family and community bonds. This kind of violence is portrayed as targeting particularly women and children, putting the men in the place of perpetrator of the rape. This works aims to approach the sexual violence as a weapon of war targeting men and boys as victims of such violence. We focus this issue in armed conflicts in the African continent as geographical space of analysis. Based on records from the international press, it seeks to understand the relations of power, dominance, and submission, established between man as perpetrator of sexual violence and man victim of rape, as well as the reasons for the invisibility of this kind of sexual violence.